Management of Eumycetoma - Tjokorde Istri Nyndia Vaniari; Sunarso Suyoso; Linda Astari; Yuri Widia; Sylvia Anggraeni; Evy Ervianti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Mycetoma is a chronic inflammatory disease of the skin that can extend to the fascia, tendons, muscles, and bones. Caused by a bacterium called actinomycetoma and a fungus called eumycetoma are responsible for mycetoma, both of which must be distinguished because they require different medical therapy. Eumycetoma is a localized disease, chronic, and growing slowly. Most of eumycetoma patients had delays in seeking medical care. Purpose: To provide an overview and discuss various aspects of eumycetoma, including its epidemiology, etiology, pathogenesis, classification, clinical picture, diagnosis, differential diagnosis, and therapy. Review: Eumycetoma infection begins as infectious agents enter through the skin with a minor trauma caused by objects contaminated with fungi, forming granular or granulomatous lesions with tract and sinus in there. The infection can spread from the site of inoculation into the muscles and bones. The diagnosis is based on anamnesis (chronic and painless), the triad of tumefaction, draining sinuses and grains, and laboratory investigation. It’s a difficult case, often recur and difficult to be surgical excisison, so that the best first option therapy is the combination of itraconazole and terbinafine itself as an alternative to surgical therapy at least 6 months. Conclusion: Eumycetoma is an infection caused by a fungus with granulomatous lesions with sinus formation and grains in it. The best first option therapy is the combination of itraconazole and terbinafine although it’s still an early case.